An SMLB-based OFDM receiver over impulsive noise environment. (20th November 2020) - Liu, Chengbo; Chen, Na; Okada, Minoru; Hou, Yafei
Abstract : The impulsive noise (IN) damages the performance of wireless communication in modern 5G scenarios such as manufacturing and automatic factories. The proposed receiver utilizes constant false alarm rate to obtain the threshold and combines with blanking to further improve the performance of the conventional blanking scheme with acceptable complexity. The simulated results show that the proposed receiver can achieve a lower bit error rate even if the probability of IN occurrence is very high and the power of the IN is much larger than that of the background noise.